Regulation of PANI nanofiber conductivity and its influence on the DC dielectric properties of LDPE. (September 2021) - Zhang, Chengcheng; Kong, Xiangqing; Liu, Wenxin; Yang, Jiaming; Zhao, Hong
Abstract: To study the effect of electrical conductivity of nanomaterials on the space charge accumulation in low density polyethylene (LDPE), doped and dedoped polyaniline (PANI) nanofibers with the same diameter and different conductivity were prepared and added into LDPE. The PANI nanofibers and nanocomposites were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscope, thermogravimetric analysis (TGA), X-ray diffraction analysis (XRD) and differential scanning calorimeter (DSC). The space charge distribution, direct current (DC) conductivity and DC breakdown strength of the nanocomposites were measured. The addition of either PANI nanofibers enhanced the crystallization, improved the space charge distribution and reduced the conductivity of LDPE. Doped PANI nanofibers had higher conductivity and could more effectively suppress space charge accumulation than dedoped PANI nanofibers. However, doped PANI nanofibers reduced the DC breakdown strength of PANI/LDPE nanocomposites. Overall, dedoped PANI nanofibers were superior for DC dielectric properties of LDPE. Highlights: Doped and dedoped PANI nanofibers have the same diameter but different conductivity. Doped PANI could better improve space charge distribution than dedoped PANI. Doped PANI would reduce the conductivity and breakdown strength. Dedoped PANI could reduce the conductivity and increase the breakdown strength. Dedoped PANI/LDPE nanocomposites could better improve DC electrical characteristics.